Two Cidian Rewritings in Contemporary Spanish Narrative: El Cid, el último héroe (1989) and ¡Mio Cid! (2007). Issue 7 (8th August 2020) - Mármol Ávila, Pedro
Abstract: Representations of the Cid have abounded in texts and other mediums since the existence of Rodrigo Díaz de Vivar, in the eleventh century. This article explores his presence in contemporary Spanish narrative by comparing two texts: José Luis Olaizola's El Cid, el último héroe (1989) and ¡Mio Cid! (2007) by Antonio Orejudo, Luisgé Martín and Rafael Reig. The differences between these representations are considerable and concern the textual basis which the authors used when composing their creations. This and other aspects demonstrate two distinct ways of comprehending and recreating the medieval knight within the framework of various specific publishing dynamics.